Common fixed-point theorems on complex partial b- metric space - Kumar Dwivedi, Dr. Pradeep (International Journal of Advanced Mathematical Sciences, 2025)
In this paper, we establish some unique common fixed-point theorems for two pairs of weakly compatible mappings in complex partial b-metric space which generalize and improves several well- known common fixed point results in partial b-metric space.